EXPERIMENTAL STUDY OF PARTICLE SIZE EFFECT ON SEPARATION EFFICIENCY OF DUAL CYCLONE SEPARATOR - Puspitasari, Dewi; Hutapea, Felix Theo Yusama (Asosiasi Peneliti Sriwijaya, 2024)
A cyclone separator is a device for separating solid particles and fluids. In this study, the performance of a cyclone separator was enhanced by adding a smaller cyclone. The objective is to separate coconut shell powder particles and determine the efficiency of the dual cyclone separator. The experiment involved varying the inlet airflow velocity to 7 m/s, 10 m/s, and 15 m/s and using different coconut shell powder particle sizes, ranging from mesh numbers 80 to 120. The results of the experiment showed that the efficiency of particle separation was significantly influenced by both the particle size and air velocity. Higher air velocity and larger particle size resulted in greater separation efficiency. The best performance was observed with the mesh particle size of 80 at an air velocity of 15 m/s, which achieved an efficiency value of 98.33%. The experiment also measured the particles' precipitated and wasted mass.